Fetal developmental trajectories following maternal immune activation are shaped by sex chromosome–gonadal interactions - Alison M. Randell; Jenna Hanrahan; Stephanie Salia; T. Nadine Burry; Lucas F. Fowler; Alexandre S. Maekawa; John G. Sled; Deepak K. Kaushik; Lindsay Cahill; Ashlyn Swift-Gallant (Proceedings of the National Academy of Sciences, 2026)
Maternal immune activation (MIA) contributes to neurodevelopmental disorders with male-biased prevalence. To disentangle the contributions of sex chromosomes (XX vs. XY) and gonads (ovaries vs. testes) in shaping fetal responses to MIA, we used the four-core genotypes (FCG) mouse model. Offspring representing all combinations of sex chromosome and gonadal status were generated and exposed to poly(I:C) or saline at embryonic day (E)12.5. We assessed maternal serum, fetal placentas, and fetal brain cytokines at E13.5; at E17.5, fetal development was evaluated via microultrasound and CT imaging. MIA induced a robust maternal inflammatory response, elevating IL-6, MCP-1 (CCL2), and TNF-α, which disrupted placental function and fetal development. Compared to all other genotypes, XX gonadal females exhibited a distinct placental proinflammatory signature that appeared largely independent of MIA exposure, along with greater umbilical artery blood flow and relatively little fetal brain inflammation, suggesting a placental buffering effect. In contrast, gonadal males demonstrated greater susceptibility to MIA-related impairments than gonadal females in umbilical artery diameter and blood flow, while XY gonadal females displayed the greatest neural inflammation following MIA. A pilot study using CT imaging suggests concurrent underdevelopment of the fetal thymus, trachea, heart ventricles, and clavicle in MIA-exposed XX gonadal males relative to gonadal females, indicating that the presence of testes/Sry in an XX chromosomal context may exacerbate MIA effects for these structures. These findings reveal that sex chromosomes and gonadal hormones both contribute to fetal resilience to MIA, offering insight into sex-specific developmental trajectories and informing strategies to protect fetal neurodevelopment.